Two Large Families of Chemoreceptor Genes in the NematodesCaenorhabditis elegans and Caenorhabditis briggsae Reveal Extensive Gene Duplication, Diversification, Movement, and Intron Loss - Robertson, Hugh M.

(untitled) (Genome Research, 1998)
The str family of genes encoding seven-transmembrane G-protein-coupled or serpentine receptors related to the ODR-10 diacetyl chemoreceptor is very large, with at least 197 members in theCaenorhabditis elegans genome. The closely relatedstl family has 43 genes, and both families are distantly related to the srd family with 55 genes. Analysis of the structures of these genes indicates that a third of them are clearly or likely pseudogenes. Preliminary surveys of other candidate chemoreceptor families indicates that as many as 800 genes and pseudogenes or 6% of the genome might encode 550 functional chemoreceptors constituting 4% of the C. elegans protein complement. Phylogenetic analyses of the str and stlfamilies, and comparisons with a few orthologs in Caenorhabditis briggsae, reveal ongoing processes of gene duplication, diversification, and movement. The reconstructed ancestral gene structures for these two families have eight introns each, four of which are homologous. Mapping of intron distributions on the phylogenetic tree reveals that each intron has been lost many times independently. Most of these introns were lost individually, which might best be explained by precise in-frame deletions involving nonhomologous recombination between short direct repeats at their termini.[Alignment of the putatively functional proteins in the str and stl families is available from Pfam (http://genome.wustl.edu/Pfam); alignments of all translations are available at http://cshl.org/gr; alignments of the genes are available from the author at hughrobe@uiuc.edu]